PARTISIPASI MASYARAKAT TERHADAP KEBERHASILAN PROGRAM PEMBUATAN KEBUN BIBIT RAKYAT (KBR) DI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Syahidul Anwar; Rosnita '; Arifudin ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the level of community’s participation in implementing the Community’s Garden Seeds Development Program (KBR) in Sub District of Bangkinang,  Kampar District, and the relationship between the factors that influence its participation. Descriptive study with a quantitative approach was used as research’s method, while 30 famers were interviewed as repondens. In term of analyzing, Summated Likert Scale Rating (SLR) was used to analyze the first objective and Rank Spearman’s Correlation to analyze the second objective. The result showed that: (1) The level of community’s participation in implementing the KBR in District Bangkinang Kampar district is high; (2) Variables of age, education, experience, fitness programs, official attention and benefits related programs affect community’s participation in KBR. Key word: Participation, Community’s Garden Seeds Development Program (KBR)